UPAYA MENINGKATKAN HASIL BELAJAR KIMIA DENGAN PENDEKATAN PROJECT-BASED LEARNING - Kurniadi, Didi; Supardi, Kasmadi Imam; -, Latifah (Jurusan Kimia, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Semarang, 2014)
The low learning outcome chemistry mainly caused by the learning process did not Â provide the opportunity for students to gain learning experience. The purpose of this research was to improve student learning outcomes with Project-Based Learning approach. This study was a class action (Class-Room Action Research). This study was conducted in two cycles, each cycle consisting of planning, action, observation, and reflection. The focus of this research was improving student learning outcomes. The data collection techniques used were technical documentation, observation and tests. Research was successful if at least 23 of the 30 students scored more than 75. The results showed that the application of Project-Based Learning approach can improve learning outcomes. Research data completeness cognitive learning outcomes cycle I was 23 of the 30 students completed, affective domain was 23 of 30 students completed and psychomotor domains was 27 of 30 students completed. Research data completeness cognitive learning outcomes cycle II was 26 of 30 students completed, the affective domain was 24 of the 30 students completed and psychomotor domains was 26 of the 30 students completed. This means that the indicator set had achieved success on the cycle II. From the research, it was concluded that implementing Project-Based Learning approach could improve student learning outcomes of chemistry.Keywords: Learning Outcome, Project-Based Learning, Purifying Of Table SaltÂ